South-South cooperation monitoring movements: engaging southern powers in Africa ‘from below’ - Trajber Waisbich, L (Oxford University Press, 2024)
This chapter investigates accountability-related mobilization practices of civil society organizations from Brazil, China, and India, alongside peer organizations in Africa. The chapter examines how these organizations engage in the politics of contestation around infrastructure projects in Africa throughout the 2010s. It provides a comparative analysis of the framings and repertoires used by civil society actors and the issues that citizen-led collective action produces in the context of expanding South-South cooperation (SSC) in Africa by rising powers. By focusing on dynamics of social mobilization in the context of Southern-led development cooperation, the chapter helps to better understanding how citizens demand and forge alternative citizen-led forms of participation and political control over this burgeoning transnational arena. In doing so, the chapter connects SSC-related mobilization dynamics to evolving state-society relations in the context of foreign policymaking in Brazil, China, and India, and how these influence African infrastructure globalities.